A hands-on introduction to big data analytics - Obembe, Funmi; Engel, Ofer (Thousand Oaks : Sage Publishing, 2024)
"This new textbook offers a hands-on introduction to big data analytics, helping you to develop the skills you need to hit the ground running as a data professional. The textbook complements theoretical foundations with an emphasis on the application of big data analytics, illustrated by real-life use cases as well as using real-life data for all examples and practice work. The book contains comprehensive coverage of all of the key topics in this area, and uses open-source technologies and examples in Python, PySpark and R"--